2000
DOI: 10.1038/sj.cgt.7700273
|View full text |Cite
|
Sign up to set email alerts
|

Induction of long-lasting cytokine effect by injection of IL-12 encoding plasmid DNA

Abstract: We have recently demonstrated that DNA coding for both subunits of the murine IL -12 heterodimer exhibits a strong antimetastatic effect against B16 -melanoma in C57BL / 6 mice and after intratumoral injection tumor regression. Here we show that the antimetastatic effect can be detected when the DNA is injected intramuscularly 30 days before tumor cell challenge. A long -term IL -12 expression was measured for up to 50 days in the serum with a peak at day 20 amounting to about 10 ng / mL in C57BL / 6 mice. CpG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 35 publications
(44 reference statements)
3
26
0
Order By: Relevance
“…injection of naked DNA of this plasmid resulted in longterm IL-12 production. 9,22 In agreement with these observations, i.m. injection 20 days prior to, or 20 days and 2 days prior to initiation of the angiogenesis assay, resulted in strong and significant angiogenesis inhibition (Figure 1b).…”
Section: Prevention Of Angiogenesis In Vivo By Il-12 Gene Therapysupporting
confidence: 85%
“…injection of naked DNA of this plasmid resulted in longterm IL-12 production. 9,22 In agreement with these observations, i.m. injection 20 days prior to, or 20 days and 2 days prior to initiation of the angiogenesis assay, resulted in strong and significant angiogenesis inhibition (Figure 1b).…”
Section: Prevention Of Angiogenesis In Vivo By Il-12 Gene Therapysupporting
confidence: 85%
“…It is unlikely that this mechanism was due to more viable tumor cells, which probably produced IL-12 by electroporation-mediated gene transfer, in immunosuppressed mice than in nonimmunosuppressed mice, because the pCAGGSmIL-12-transferred tumor volume, necrotic area, and number of tumor neovascularizations were comparable between nonimmunosuppressed mice and immunosuppressed mice. Considering a report suggesting that long-lasting IL-12 production by injection of IL-12-encoding plasmid DNA due to an autocrine or paracrine positive feedback mechanism whereby several cell population including NK cells are involved (52), long-lasting IL-12 production in our present study may also be due to the positive feedback mechanism by which the production of endogenous IL-12 is actually produced by host macrophages and dendritic cells. Moreover, Conboy et al (48) reported that FK506, a calcineurin inhibitor, acts in macrophages and fibroblasts to augment cytokines, IL-12 and TNF-␣, and this effect is paradoxical compared with that in naive T cells.…”
Section: Discussionsupporting
confidence: 51%
“…The use of IL-12 has generated significant interest in the field of tumor immunotherapy and on the basis of successful results obtained in preclinical models has been tested in Phase I and II clinical trials [13][14][15][16][17]. Several approaches have focused on the local release of IL-12 at the site of a tumor via methods including IL-12 transfected fibroblasts or DC [18] [19], in vivo transfection of tumor cells via viral vectors [20][21][22][23][24][25][26], or electroporation of plasmid DNA [4,[27][28][29][30]. Beyond the technical complexities and potential complications of these approaches, the clinical results have been disappointing and have dampened enthusiasm for intratumoral cytokine-based immunotherapies.…”
Section: Discussionmentioning
confidence: 99%
“…RENCA is an immunogenic murine renal cell carcinoma of spontaneous origin in the Balb/c strain [4]. Cell lines were maintained in complete media consisting of RPMI 1640 supplemented with 10% heatactivated fetal bovine serum, 0.1 mM nonessential amino acids, 1 lM sodium pyruvate, 100 lg/ml streptomycin, 100 units/ml penicillin, 50 lg/ml gentamycin and 0.5 lg/ml fungizone, all from Life Technologies, Inc. (Grand Island, NY).…”
Section: Methodsmentioning
confidence: 99%